2015
DOI: 10.1038/ismej.2015.176
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous composition of key metabolic gene clusters in a vent mussel symbiont population

Abstract: Chemosynthetic symbiosis is one of the successful systems for adapting to a wide range of habitats including extreme environments, and the metabolic capabilities of symbionts enable host organisms to expand their habitat ranges. However, our understanding of the adaptive strategies that enable symbiotic organisms to expand their habitats is still fragmentary. Here, we report that a single-ribotype endosymbiont population in an individual of the host vent mussel, Bathymodiolus septemdierum has heterogeneous gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 38 publications
3
86
0
Order By: Relevance
“…Based on the FISH and immunohistochemistry analyses and the radioisotope-labeled bicarbonate tracer experiments, Petersen et al [13] pointed out that hydrogenotrophy may serve as primary energy metabolism competitively with thiotrophy in the chemosynthetic holobiont. In addition, it has been reported that some chemosynthetic holobionts may use H 2 as an energy source because the genes encoding hydrogenase, and even the expression of the genes, were found in the symbiont genomes and transcriptomes [14,[16][17][18][19][20]. However, it has been also shown that these holobionts have molecular and physiological potentials of other energy metabolisms (sulfur and/or methane oxidation).…”
Section: Conclusive Remarks and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the FISH and immunohistochemistry analyses and the radioisotope-labeled bicarbonate tracer experiments, Petersen et al [13] pointed out that hydrogenotrophy may serve as primary energy metabolism competitively with thiotrophy in the chemosynthetic holobiont. In addition, it has been reported that some chemosynthetic holobionts may use H 2 as an energy source because the genes encoding hydrogenase, and even the expression of the genes, were found in the symbiont genomes and transcriptomes [14,[16][17][18][19][20]. However, it has been also shown that these holobionts have molecular and physiological potentials of other energy metabolisms (sulfur and/or methane oxidation).…”
Section: Conclusive Remarks and Future Perspectivesmentioning
confidence: 99%
“…Subsequently, based on the newly developed in situ RNA extracting instrument and metatranscriptomic analysis, Sanders et al also demonstrated that some of the Sulfurimonas endosymbionts in Campylobacterota [15] expressed genes of Ni-Fe-hydrogenase in the northern ELSC vent fields with relatively abundant H 2 , implying that the specific Alviniconcha holobionts would also utilize H 2 as their chemosynthetic energy source [14,16]. Ikuta et al [17] also demonstrated that hupL and hupS genes, which encode small and large subunits of hydrogenase, were expressed in the symbiont of Bathymodiolus septemdierum from the Myojin Knoll hydrothermal vent site. In addition, genome-sequence analyses demonstrated that several holobionts of ventendemic chemosynthetic invertebrates have genes that are potentially involved in H 2 -oxidization, although the functional and molecular information of these genes is still not known [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In our model, bacteria are acquired from the environmental symbiont pool in juveniles 44 . The presence of a symbiont environmental pool was suggested before based on the detection of symbiont genes in adjacent seawater 45,46 . Nevertheless, the loss of central metabolic enzymes suggests that bacteria disperse in a dormant state 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The new tissue is colonized by a self-infection process 26 , which involves infection of the newly formed filaments via endocytosis with bacteria that are released from old tissue via exocytosis (2). The spatial distribution of strains within the gill tissue also supports self-infection 45 . The continuous self-infection process imposes serial founder effects that lead to a reduction in strain diversity, which is mostly driven by drift.…”
Section: Pn/ps and Neutrality Index Estimationmentioning
confidence: 95%
“…In turn, the common presence of chemosynthetic symbiont in vent marine mussels inahibing extreme environments (e.g. Ikuta et al 2016) is the evidence for the support of host fitness benefits associated with the presence of symbionts (Zug and Hammerstein 2018).…”
Section: Introductionmentioning
confidence: 99%